MENINGKATKAN MOTIVASI BELAJAR SISWA MELALUI MODEL PEMBELAJARAN SNOWBALL THROWING PADA PEMBELAJARAN PPKN KELAS X-6 SMAN 14 MEDAN - Fransisco, Anwar; Kesuma, Sapta; Gultom, Rumesti (Jurnal Dedikasi Pendidikan, 2025)
Student learning motivation is one of the important factors that influences the success of the learning process. Based on initial observations at SMAN 14 Medan. In class This research aims to foster students' learning motivation by applying the Snowball Throwing learning model in Civics lessons. This research was conducted in class X-6 at SMAN 14 Medan with a total of 35 students. This research is classroom action research. The data analysis technique used is quantitative descriptive. This research consists of cycle one and cycle two. Research data was taken from observations and student learning motivation questionnaires. The results of the research show that the percentage of students' learning motivation in the first cycle was 65% and in the second cycle it increased to 80%. So it can be concluded that the existence of the Snowball learning model increases students' learning motivation in class X-6 at SMAN 14 Medan.